The State and the Prospects of Railway Development in Croatia - Šiljković, Željka; Glamuzina, Martin; Topolnik, Dražen (Promet - Traffic&Transportation, 2012)
The authors consider the existing state of railway transportin Croatia which is characterised by insufficient developmentand backward technology. These make specific obstructionsfor the Croatian joining of the trans-European integration processes.A solution that would make Croatia an important nodein linking the European East and West, i.e. South and North isproposed. In this way two leading centres would be activated:Zagreb and Rijeka. Regarding inland transversal/inking priorityis given to modernisation and reconstruction of an essentialdirection ofCroatian North and South which links two leadingindustrial and population centres: Zagreb and Split.This would enable the economic and social revival of Dalmatianinfluence within Croatian economy.